HISTORIOGRAPHY OF RELIGIOUS MODERATION (RELATIONSHIP BETWEEN TJONG A FIE AND ISLAM IN NORTH SUMATRA 1880-1990) - Mhd. Hanafi Hasibuan; Hotmatua Paralihan (Program Pascasarjana UIN Sumatera Utara, 2025)
This research examines the historiography of religious moderation through the relationship between Tjong A Fie and Islam in North Sumatra from 1880-1990. The main problem addresses the scarcity of in-depth studies on the role of non-Muslim figures in promoting interfaith harmony amidst historiography dominated by conflict narratives. Employing the historical method-including heuristics, criticism, interpretation, and historiography-this study aims to uncover how Tjong A Fie, a Chinese entrepreneur, contributed to the development of Muslim communities and facilitated interfaith dialogue. Key findings indicate that Tjong A Fie actively supported the construction of Islamic worship facilities, funded religious activities, and built strong relationships with local religious scholars, creating a pragmatic and inclusive model of religious moderation. The conclusion reveals that his contributions offer a fresh perspective on the history of religious moderation in North Sumatra, highlighting the importance of non-formal leadership and philanthropy in shaping social cohesion.